2011
DOI: 10.1149/1.3630837
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Challenges of EUV Mask Substrates, Blanks, and Patterned Mask

Abstract: SEMATECH has been a pioneer in EUV mask substrate and blank cleaning since early 2003. Nevertheless, EUV mask blank defectivity remains one of the main challenges in realizing EUV lithography. EUV masks have their own cleaning challenges that are partly related to introducing new materials and partly related to cleaning-induced EUV reflectivity changes in the multilayer structure. Removal of sub-20 nm particles from the surface of EUV mask substrates without leaving pits is a major challenge along with maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Cleaning methods for EUV photomasks can be classified into three categories: physical cleaning, which employs megasonic waves in conjunction with a standard clean-1 (SC-1) solution; wet cleaning, which uses solutions such as sulfuric acid-hydrogen peroxide mixture (SPM) or SC-1; and dry cleaning, which utilizes O 2 plasma ashing or UV/ Ozone exposure. Rastegar et al reported that physical cleaning with megasonic waves operates via two primary mechanisms: microstreaming and megasonic cavitation collapse, with the latter inflicting physical damage on the photomask surface [14]. Belau et al found that both the reflectivity and durability of EUV photomasks degrade due to etching and oxidation during dry cleaning processes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning methods for EUV photomasks can be classified into three categories: physical cleaning, which employs megasonic waves in conjunction with a standard clean-1 (SC-1) solution; wet cleaning, which uses solutions such as sulfuric acid-hydrogen peroxide mixture (SPM) or SC-1; and dry cleaning, which utilizes O 2 plasma ashing or UV/ Ozone exposure. Rastegar et al reported that physical cleaning with megasonic waves operates via two primary mechanisms: microstreaming and megasonic cavitation collapse, with the latter inflicting physical damage on the photomask surface [14]. Belau et al found that both the reflectivity and durability of EUV photomasks degrade due to etching and oxidation during dry cleaning processes [15].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned at Introduction, there appear very various material surfaces to be cleaned at the same time in front and backend processes of EUV semiconductor technology such as metals, compounds, and low and high k dielectrics of various chemical forms of hydrides, hydrates, oxides, nitrides, carbides and so on. 21,22 Therefore, the wet cleaning requirements now become more stringent in view of EUV cleaning and rinsing concepts as well as of oxide formation before the following process step of nano-scale device fabrication. It has already been proven that cathode water showed the excellent performance for commercial application to clean the contaminated Sn on EUV mask.…”
mentioning
confidence: 99%
“…9 This damage creation is also a major bottleneck for EUV mask cleaning processes. 10 In this paper, a discussion of the fea-sibility of physical cleaning is given. Next, an overview of megasonic cleaning is presented, followed by a future outlook.…”
mentioning
confidence: 99%